Solitary Wave-Series Solutions to Non-Linear Schrodinger Equations - Azram, Muhammad; Zaman, H. (IIUM Engineering Journal, 2012)
ABSTRACT: In this paper, higher-order dispersive non-linear Schrodinger equations are studied. Their solitary wave-series solutions with continuity of the derivatives and specific discontinuity of the derivatives at the crest are presented. Furthermore, convergence of the seriesâ€™ solutions is also validated and discussed with the help of graphs.Â  ABSTRAK: Kertas ini mengkaji persamaan Schrodinger serakan taklinear turutan tinggi. Penyelesaian siri-gelombang tunggalnya dengan kamiran berterusan dan kamiran tak berterusan pada maksimum telah dibentangkan. Penumpuan penyelesaian siri juga telah diperiksa dan dibincangkan dengan bantuan graf-graf. KEYWORDS: Schrodinger equation; solitary wave-series solution; continuity and discontinuity of derivatives at crest